PENGEMBANGAN SDM KESEHATAN: MEMBANGUN KAPASITAS MELALUI PELATIHAN DAN PENGEMBANGAN BERKELANJUTAN LITERATURE REVIEW - Adinda Kurnia Herlambang; Nikita Alia Rajebta; Anggraeni Dian Ciptaningrum; Riswandy Wasir; Cahya Arbitera (Universitas Bina Taruna Gorontalo, 2025)
This research aims to provide an overview of health human resource development through training methods. So that it can see the strengths and weaknesses of existing training methods. The development of health human resources through training and continuous development is very important in determining the success or failure of an organisation. Health workers have an important and responsible role in maximising the quality of health services to the community, increasing awareness, motivation and ability to live healthy, and helping them achieve the highest level of health. The method used in this research is literature review using databases from Google Scholar for national articles and Pubmed for international articles. The articles found said that HR training needs to be held to support the competence of health workers. development is one of the efforts to improve human resources through training or education programmes. Training and continuing education of health workers have an important role in improving the quality and motivation of work. Training programmes can provide new knowledge and skills that improve the ability of workers in the health sector.